Genetic dissection of a stem cell niche: the case of the Drosophila ovary. - Bolivar, J.; Pearson, J.; Lopez-Onieva, L.; Gonzalez-Reyes, A. (Developmental Dynamics, 2006)
In this work, we demonstrate a powerful new tool for the manipulation of the stromal component of a well-established Drosophila stem cell niche. We have generated a bric-a-brac 1 (bab1)-Gal4 line that drives UAS expression in many somatic ovary cell types from early larval stages. Using this Gal4 line, we could effectively induce FLP/FRT-mediated recombination in the stromal cells of the ovarian germline stem cell niche. Mutant clones were observed in the developing ovary of larvae and pupae, including in somatic cell types that do not divide in the adult, such as the cap cells and the terminal filament cells. Exploiting the ability of bab1-Gal4 to generate large clones, we demonstrate that bab1-Gal4 is an effective tool for analyzing stem cell niche morphogenesis and cyst formation in the germarium. We have identified a novel requirement for engrailed in the correct organization of the terminal filaments. We also demonstrate an involvement for integrins in cyst formation and follicle cell encapsulation. Finally using bab1-Gal4 in conjunction with the Gal80 system, we show that while ectopic dpp expression from stromal cells is sufficient to induce hyperplastic stem cell growth, neither activation nor inactivation of the BMP pathway within stromal cells affects germline stem cell maintenance.